The preferred mode of delivery of medical professionals and non-medical professional mothers-to-be and the impact of additional information on their decision: an online questionnaire cohort study - Bihler, Julia; Wallwiener, Stephanie; Wallwiener, Markus; Sohn, Christof (Archives of gynecology and obstetrics, 2019)
Purpose: It was the aim to evaluate the personal preference of mode of delivery and to analyze differences between medical professionals and non-medical professionals. Interest in participating in a risk stratification system was evaluated. We hypothesized that gaining information about risk stratification provided in the survey could potentially change participants’ decision regarding the preferred mode of delivery; therefore, subjects were asked twice (before and after providing information). Methods: Five cohorts [four professionals (MP) including participants of the German Urogynecology Congress 2017, employees of two major university hospitals in Germany, and members of the German Society of Gynecology and Obstetrics, and one non-professional group (NP) including pregnant women] were invited online to participate in this survey. Results: Vaginal delivery was the preferred mode of delivery in both groups (MP 90.4% vs. NP 88.8%; p = 0.429). MP are more likely to opt for CS due to concerns regarding pelvic floor disorders (MP 56.6% vs. NP 9.1%; p < 0.001). Likewise, parity and prior experienced CS (pCS) had a significant impact on the decision towards vaginal delivery (parity MP OR 7.5 95% CI 4.6-12.3, NP OR 9.3 95% CI 1.9-44.2; (pCS) MP OR 0.12 95% CI 0.07-0.19, NP OR 0.05 95% CI 0.01-0.25). There is great interest in participating in risk stratification systems in the majority of participants (68.9%). Conclusions: MP and NP prefer vaginal birth for themselves or their partners. Within the group that opted for CS, MP were significantly more often concerned about pelvic floor disorders. Future prevention aspects might include education about pelvic floor disorders.
First Online: 22 November 2018
Gesehen am 13.09.2019